Gosudarstvennyj naucno-issledovatels'skij institut social'no-ekonomiceskich problem i sportivno-ozdorovitel'nych technologii - Mar'janovic, A. T. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The article concerns significance of the different methods of sport training, as well as the scientific technologies used to gain for the best results of athletes. Since 1978 the research center in Lesshaft St. Petersburg State Uni-versity of the physical culture have been working on the projects connected with sports technologies. The goals of the State Research Institute of Social-economical problems and sport-imporovement technologies are set forth, namely the chronobiological research (Shaposhnikova V. A.), the development of the immunomodulatory drugs (Medvedev Yu. V.) and sport training gears (Golub V. Ya., Kovalev S. N et al.). All of these proposals may be widely introduced in the sport training practice.